Evaluate the Implementation of Educational Curriculum and Lecturer’s Knowledge about the Blueprint to the UKNI’s Graduation Rate in South Sulawesi - Mushawwir, Ahmad; Tahir, Takdir; Kadar, Kusrini (International Journal of Psychosocial Rehabilitation, 2020)
Indonesian Nurse Competency Test (UKNI) is a process of measuring knowledge, skills and behavior of students in tertiary institutions conducting nursing study programs with the aim to achieve graduate competency standards that meet the competency standards of working. As many as 24 nursing study programs in South Sulawesi took UKNI’s graduation test, but unfortunately in three periods of UKNI’s implementation, therate only reached 32.49%, this result was lower than the UKNI’s national scale which reached 36%. This research design was the type ofquantitative correlation that examined and revealed the relationship between the role of institutions and graduation’s rates of UKNI. The sample of population in this study was 95 permanent nursing lecturers from 18 nursing study programs in South Sulawesi. Correlation test were chi-square and fishery with the significant level of p-valuation showed that there were the relationship between the implementation of the undergraduate curriculum (p = 0.009), the implementation of the Professional curriculum (p = 0.03), lecturers' knowledge of the UKNI blue print (p = 0.01), and the guidance / enrichment of UKNI (p = 0.00) with graduation’s rates of nurses’ competency test. Research conclusions showed that the role of the institution was closely related to the level of students’ graduation in competency tests. Further research is necessary to be carried out to specifically analyze every role run by the institution that affects the difference in students’ graduation level of each study program at UKNI.